(untitled) (Cultural Diversity: Journal of Anthropology and Cultural Heritage, 2024)
In the research relating to beliatn sentiu, a lot of factors emerge that form the process of harmonization with the locals that ensures the existence of said rituals in the modern world. This research aims to provide a general understanding of the socio-cultural situation of the Dayak Benuaq pertaining to Beliatn Sentiu to minimize and mitigate conflicts within the Dayak Benuaq society. Using a qualitative and descriptive approach in describing the situations pertaining to beliatn sentiu, observation, literature review, and interviews are used to answer the relevance of beliatn sentiu in the Dayak Benuaq community, how beliatn sentiu harmonized with it’s social surrounding, and to describe the procedures of beliatn sentiu. Beliatn sentiu is still very much relevant in the life of the Dayak Benuaq community due to the religious belief of the Dayak Benuaq, the individual push to be healed from ailments by any way necessary, and the lack of access to healthcare facilities in certain areas. Beliatn sentiu isn’t only a ritual that is run by many generations, but it also have an intrisict value which form a community together like social, cultural, economic, and artistic value. Although there’s a conflict potential due to a clash between religion and the traditional belief.